2018
DOI: 10.1002/pc.25107
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and performance of a polyurethane hybrid composite with waste red mud

Abstract: Polyurethane-based organic-inorganic hybrid composite is attracting increasing attention due to its excellent performance and low cost. Herein, a facile and effective strategy has been proposed for the fabrication of polyurethane/red mud hybrid composite by anchoring red mud particles into a polyurethane frame. The resulting hybrid composite was mainly composed of amorphous polyurethane and crystalline red mud, and its probable formation mechanism was proposed. The polyurethane/ red mud composite with micron p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 27 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Figure shows the XRD patterns of the grouting materials containing different catalysts. Their main phases observed after the curing reaction are as follows: the PU matrix at 2θ = 20°; polysilicic acid particles at 2θ = 29.1°, 33.8°, and 36.9°; Na 2 CO 3 at 27.9°, 31.7°, 40°, 45.5°, and 51.3°; and NaHCO 3 at 2θ = 30.4°, 44.6°, and 52.5° . It should be noted that the peaks corresponding to the polysilicic acid, Na 2 CO 3 , and NaHCO 3 phases are very sharp, indicating their highly crystalline morphologies.…”
Section: Resultsmentioning
confidence: 97%
“…Figure shows the XRD patterns of the grouting materials containing different catalysts. Their main phases observed after the curing reaction are as follows: the PU matrix at 2θ = 20°; polysilicic acid particles at 2θ = 29.1°, 33.8°, and 36.9°; Na 2 CO 3 at 27.9°, 31.7°, 40°, 45.5°, and 51.3°; and NaHCO 3 at 2θ = 30.4°, 44.6°, and 52.5° . It should be noted that the peaks corresponding to the polysilicic acid, Na 2 CO 3 , and NaHCO 3 phases are very sharp, indicating their highly crystalline morphologies.…”
Section: Resultsmentioning
confidence: 97%
“…A PU and red mud composite, the mud in micron particles uniformly embedded in PU, exhibited satisfactory mechanical performance and the compressive and flexural strength are, after complete curing, up to 38.6 and 12.4 MPa. It also displayed very good thermal stability, flame retardancy, storage stability, and reinforcement [60]. The heat conducting with focus on the enhancement of thermal conductivity of WPU composites through compatibility and feasibility of hybrid techniques is reviewed [61].…”
Section: Compositesmentioning
confidence: 99%
“…Polyurethane-urea is widely used as grouting materials in the mining industry [1][2][3][4] , building foundation reinforcement [5][6][7] and road maintenance [8][9][10][11][12] , because of its excellent characteristics in terms of e cient performance and easy operation. However, it is found that the high cost, high heat release and ammability of polyurethane-urea production limit its application.…”
Section: Introductionmentioning
confidence: 99%